A method for preparing carbon composite nano cobalt sulfide by short process using organic clean cobalt slag and its application

Through the low-temperature roasting process of pickling and zinc removal and oxygen-free atmosphere, carbon composite cobalt sulfide materials were prepared, which solved the pollution problem in the roasting-leaching process, and realized the efficient resource utilization of organic clean cobalt slag and the application of high-performance battery materials. .

CN118833872BActive Publication Date: 2024-12-13XIANGJIANG LAB
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411305227.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2024-12-13
Estimated Expiration
2044-09-19

AI Technical Summary

Technical Problem

When the existing roasting-leaching process recovers cobalt in organic net cobalt slag, polluting gases such as nitrogen oxides and sulfur dioxide will be produced, and high-valent cobalt oxide is difficult to effectively leaching, resulting in the comprehensive utilization of cobalt resources not being industrialized.

Method used

The short process of low-temperature roasting in a pickled zinc-free atmosphere is adopted to remove zinc and other elements from the organic pure cobalt slag, and carbon composite cobalt sulfide materials are prepared to avoid the formation of nitrogen oxides and sulfur dioxide, and block them through the step-by-step heating process. The contact between oxygen and nitrogen achieves efficient recycling and resource utilization of cobalt.

Benefits of technology

Effectively avoid the production of nitrogen oxides and sulfur dioxide, realize the efficient resource utilization of organic net cobalt slag, reduce pollution emissions, and provide high-performance carbon composite nano cobalt sulfide materials for the negative electrode of ion batteries, which improves the addition of resources. value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118833872B_ABST
    Figure CN118833872B_ABST
Patent Text Reader

Abstract

The present invention provides a method for preparing carbon composite nano cobalt sulfide by short process of organic clean cobalt slag and its application, which belongs to the field of resource environment and new energy battery materials; it includes two steps of acid leaching to remove zinc and low-temperature roasting in oxygen-free atmosphere, realizing the conversion of 98.8% of Fumei cobalt into carbon composite nano cobalt sulfide, and developing and utilizing it as energy storage battery material with high value. It has the advantages of short process flow, high comprehensive utilization rate of cobalt resources, no generation of nitrogen oxides and sulfur oxides, and comprehensive utilization of by-products. The obtained carbon composite nano cobalt sulfide material and its application in the field of battery materials are due to the nano-scale particle size and ultra-thin carbon layer structure of the obtained carbon composite nano cobalt sulfide, short diffusion path of lithium ions in the material, large migration rate, high contribution rate of pseudocapacitive behavior, and 0.1 A g ‑1 After 100 cycles, the discharge capacity is as high as 1198.2 mAh g ‑1 , which is much higher than the theoretical value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of resource environment and new energy battery materials, and specifically relates to a method for preparing carbon composite nano cobalt sulfide by a short process using organic clean cobalt slag and application thereof. Background Art

[0002] Cobalt is a steel-gray ferromagnetic metal, known as "industrial MSG" and "industrial teeth". It is widely used in machinery manufacturing, electronic appliances, aerospace, battery manufacturing and other industries. According to the "Analysis Report on the Supply and Demand Situation of Major Mineral Products (2020)" released by the Institute of Natural Resources Economics, my country's cobalt consumption has ranked first in the world since 2007. However, my country's primary cobalt resources are mainly associated ores, accounting for only 1.1% of the global reserves, and its external dependence is as high as more than 90%. Therefore, it is urgent to develop diversified cobalt resource supply channels, reduce my country's external dependence on cobalt resources, and improve the security of resource supply chain and energy supply.

[0003] Hydrometallurgy is the most important zinc smelting method today, and its output accounts for more than 85% of the world's total zinc output. Since cobalt is a harmful impurity in the hydrometallurgy process, it causes the "burning plate" problem in the subsequent zinc electrowinning process. Therefore, cobalt ions need to be purified and removed before zinc electrowinning. The clean cobalt slag obtained by removing cobalt has the characteristics of high grade and high output. Although the zinc powder replacement method has been used in industry for many years, due to the problems of large zinc powder consumption, expensive reagents and high cost, it has been gradually replaced by a new organic cobalt removal agent sodium fumei in recent years. The industrial application is becoming more and more extensive, which also makes the output of organic clean cobalt slag increase year by year. The cobalt in the organic clean cobalt slag mainly exists in the form of organic chelates, which is difficult to leach by conventional methods. However, its cobalt content is as high as 0.5% to 6%, which is much higher than that of ordinary cobalt ore. Therefore, the comprehensive utilization of this type of cobalt resources has received great attention from scholars. However, since the Fumei cobalt slag contains a large amount of N and S, the traditional "roasting-leaching" process for recovering cobalt will produce polluting gases such as nitrogen oxides and sulfur dioxide, and the high-valent cobalt oxide after roasting is extremely difficult to leach. The comprehensive utilization of this type of resources has never been industrialized. Summary of the invention

[0004] In order to solve the key technical problem that the existing "roasting-leaching" process for recovering cobalt from organic purified cobalt slag will produce polluting gases such as nitrogen oxides and sulfur dioxide, this scheme provides a method for preparing carbon-composite nano-cobalt sulfide from organic clean cobalt slag in a short process and its application, and utilizes the "acid washing to remove zinc and low-temperature roasting in an oxygen-free atmosphere" short-process process to recover cobalt from organic clean cobalt slag, obtain carbon-composite nano-cobalt sulfide materials and use them as negative electrode materials for ion batteries, thereby achieving efficient recovery of cobalt resources in organic clean cobalt slag and short-process high-value and resource-based applications, which can not only solve the problem of waste slag pollution, but also provide a certain degree of relief for the current shortage of cobalt resources in my country.

[0005] To achieve the above object, the present invention first provides a method for preparing carbon composite nano-cobalt sulfide by using organic clean cobalt slag in a short process, comprising the following steps:

[0006] S1. A pickling process removes zinc and other elements in the organic clean cobalt slag to obtain a pickling leaching solution and pickling slag;

[0007] S2, transporting the pickling leaching solution obtained in S1 to a zinc electrodeposition system for zinc resource recovery;

[0008] S3, placing the pickled slag obtained in S1 in an oxygen-free atmosphere and roasting it in two stages and then cooling it naturally to obtain a carbon composite nano-cobalt sulfide material and an organic gas;

[0009] S4, transporting the organic gas obtained in S3 to the sodium fumei preparation system.

[0010] Preferably, the oxygen-free atmosphere in step S3 includes nitrogen or argon.

[0011] Preferably, in the two-stage calcination in step S3, the heating rate of the first stage calcination is 1-5°C / min, the temperature is raised to 70-300°C and kept warm for 0.1-3 h, and the heating rate of the second stage calcination is 1-10°C / min, the temperature is raised to 300-1000°C and kept warm for 0.1-6 h.

[0012] Based on a general inventive concept, the present invention also provides an application of carbon-composite nano-cobalt sulfide in the preparation of high-performance battery materials.

[0013] Preferably, the battery material is an ion battery negative electrode material.

[0014] The principle of preparing carbon composite nano-cobalt sulfide material in the present invention is as follows:

[0015] The decomposition of zinc ziram in organic clean cobalt slag is achieved by dilute sulfuric acid. The two S atoms on sodium ziram (CH3)2NCSS) exist in the form of thioketone bond (C=S) and thioether bond (-S-) respectively. The electron delocalization effect makes the negative charge of the thiol group evenly distributed on the two S atoms. Therefore, when the sodium ziram anion reacts with the metal ion, the metal with a planar square or octahedral bonding orbital is easy to form a four-membered chelate ring with it. The two S atoms play an equal role and are relatively stable. 3 The tetrahedral metal ions (Zn 2+ ) and (CH3)2NCSS)-, the complex is slightly less stable. In addition, the bond angle between the two S atoms of the thiol surfactant is 92°, and the metal atom (Co 2+ ) has a bond angle of 90°, while the tetrahedral structure (Zn 2+) has a metal ion bond angle of up to 109º. ​​The above reasons lead to (CH3)2NCSS)2Co having stronger stability than (CH3)2NCSS)2Zn. In acidic solution, the chemical bond between the CS bond and Zn in the zinc chelate (CH3)2NCSS)2Zn in the organic purification cobalt slag is easy to break at a solution pH of 2~2.5, and zinc enters the solution. (CH3)2NCSS)2Co continues to exist in the form of a stable chelate when the solution pH is 2~2.5, thereby achieving the purpose of acid washing and separation of zinc and cobalt.

[0016] The decomposition and removal rate of zinc ziram by this method is above 95%. The washing liquid is a zinc sulfate solution, and the zinc carbonate byproduct can be recovered. The carbon disulfide produced is directly returned to the preparation stage of sodium ziram, and no waste gas is generated. Cobalt ziram ((CH3)2NCSS)2Co) in the pickling slag is a heterogeneous structure composed of cobalt sulfide nanodots and hydrocarbon chains (CH3)2NCSS), which can be used as a sulfur source, metal source and carbon source for carbon-coated metal sulfides without the need for adding other reactants.

[0017] In the oxygen-free high-temperature atmosphere, the pickling slag will be modified in situ by cobalt sulfide nanodots, and the cobalt sulfide nanodots will undergo crystal growth and crystal form perfection. The hydrocarbon structure will be converted into an amorphous carbon layer that covers the outside of the cobalt sulfide nanodot particles, prevents the aggregation of cobalt sulfide nanodots, and promotes the maintenance of the nanostructure of cobalt sulfide nanodots. The modified cobalt sulfide nanodots are carbon composite metal sulfide nanodots, which can be used as a high-energy density negative electrode material for lithium-ion batteries. Since the H element is required to be as low as possible when used as a negative electrode material for lithium-ion batteries, and the bond energy of the CH bond (414) is higher than that of the CN bond (305) and the CS bond (272), the CN bond and the CS bond will break during the heating process to remove H, generating carbon disulfide and nitrogen. Compared with the ordinary calcination method, no nitrogen oxides and sulfur oxides are generated. Carbon disulfide and other gases can be returned to prepare sodium fumer, realizing the recycling of sodium fumer.

[0018] Organic clean cobalt slag contains a large amount of non-metallic elements such as N, S, and C, which will produce a large amount of pollutants such as nitrogen oxides and sulfur dioxide during the conventional roasting process. The present invention roasts in an oxygen-free atmosphere and adopts a step-by-step heating process to avoid the contact between nitrogen and sulfur and oxygen-containing substances, removes oxygen in the roasting atmosphere through oxygen-free gas, and blocks the generation reaction of nitrogen oxides and sulfur oxides.

[0019] The heating process includes a heating stage, a heat preservation stage, a second heating stage and a second heat preservation stage. The first heat preservation temperature must be higher than the water evaporation temperature, but not higher than the decomposition temperature of organic gases such as carbon disulfide generated by the decomposition of fumei cobalt. By removing the water and oxygen source in the system before the decomposition of fumei cobalt, the generation reaction of nitrogen oxides and sulfur oxides can be avoided.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] (1) The method provided in this scheme for converting formate cobalt in organic clean cobalt slag into carbon-composite nano-cobalt sulfide solves the problem of serious three wastes in the resource utilization process of organic clean cobalt slag. It has broad industrial prospects and can reduce the stockpile of more than 5,000 tons of organic clean cobalt slag each year and realize its resource utilization.

[0022] (2) The method provided in this scheme for preventing the secondary pollution of nitrogen oxides and sulfur oxides generated during the roasting process of organic clean cobalt slag can effectively avoid the generation of nitrogen oxides and sulfur oxides. Organic clean cobalt slag contains a large amount of non-metallic elements such as N, S, and C, and will produce a large amount of pollutants such as nitrogen oxides and sulfur dioxide during the conventional roasting process. This scheme roasts in an oxygen-free atmosphere and adopts a step-by-step heating process to avoid the contact between nitrogen and sulfur and oxygen-containing substances, thereby reducing the emission of 3452 t SO2 and 810 tNO per year.

[0023] (3) The carbon composite nano-cobalt sulfide material provided in this scheme has nano-scale particle size, ultra-thin carbon layer structure, interface CS-Co bond, N and S doping. This type of material has a wide range of applications in optoelectronics, energy storage and other fields, and has high added value.

[0024] (4) The carbon composite nano-cobalt sulfide material provided in this scheme is used as a high-performance battery material. Due to the nano-scale particle size, ultra-thin carbon layer structure, interface CS-Co bond, N and S doping of the obtained carbon composite nano-cobalt sulfide, the lithium ion diffusion path in the material is short, the migration rate is large, and the pseudocapacitive behavior contribution rate is high. It can be used in lithium-ion batteries, lithium-ion supercapacitors, sodium-ion batteries, sodium-ion supercapacitors and aqueous capacitors as negative electrode lithium or sodium storage materials, with high added value. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0026] Figure 1 is a process flow chart of the method for preparing carbon composite nano-cobalt sulfide in Example 1;

[0027] Figure 2 It is a chemical reaction mechanism diagram of pickling and zinc removal in step S1 of Example 1;

[0028] Figure 3 This is a mechanism diagram of preparing carbon composite nano-cobalt sulfide from pickled slag in step S3 of Example 1;

[0029] Figure 4 is the XRD pattern of carbon composite nano-cobalt sulfide in Experimental Example 1;

[0030] Figure 5 is the TGA curve of carbon composite nano-cobalt sulfide of Experimental Example 1;

[0031] Figure 6 is the Raman spectrum of carbon composite nano-cobalt sulfide of Experimental Example 1;

[0032] Figure 7 is a SEM image of carbon composite nano-cobalt sulfide in Experimental Example 1, with a scale bar of 200 nm;

[0033] Figure 8 This is the TEM image of carbon composite nano-cobalt sulfide in Experimental Example 1. Figure 8 A is a TEM image with a scale of 10 nm. Figure 8 B is the TEM image with a scale bar of 5 nm;

[0034] Fig. 9 This is the EDS spectrum of carbon composite nano-cobalt sulfide of Experimental Example 1;

[0035] Fig.10 is the XPS spectrum of carbon composite nano-cobalt sulfide in Experimental Example 1, wherein (a) is the Co 2p high-resolution spectrum, (b) is the S2p high-resolution spectrum, (c) is the C 1s high-resolution spectrum, and (d) is the N 1s high-resolution spectrum;

[0036] Fig.11 The carbon composite nano-cobalt sulfide in Experimental Example 2 is 0.1A g -1 The discharge capacity at the current density of

[0037] Fig.12 The carbon composite nano-cobalt sulfide in Experimental Example 2 is 2A g -1 Long cycle performance curve at current density;

[0038] Fig.13 The carbon composite nano-cobalt sulfide in Experimental Example 2 is 5A g -1 Long cycle performance curve at current density;

[0039] Fig.14 The carbon composite nano-cobalt sulfide in Experimental Example 2 was 0.1, 0.5, 1, 2, 5, 10, 15 and 0.1A g -1 Discharge specific capacity under step current density;

[0040] Fig.15 is the XRD pattern of carbon composite nano-cobalt sulfide in Experimental Example 3;

[0041] Fig.16is the SEM image of carbon composite nano-cobalt sulfide of Experimental Example 3, scale bar 200nm;

[0042] Fig.17 The carbon composite nano-cobalt sulfide in Experimental Example 4 is 0.1A g -1 The discharge capacity at the current density of

[0043] Fig.18 is a SEM image of carbon composite nano-cobalt sulfide in Experimental Example 5, with a scale bar of 200 nm;

[0044] Fig.19 The carbon composite nano-cobalt sulfide in Experimental Example 6 is 0.2A g -1 The discharge capacity at the current density of

[0045] Fig. 20 is the SEM image of carbon composite nano-cobalt sulfide in Experimental Example 7, with a scale bar of 200 nm;

[0046] Fig.21 The carbon composite nano-cobalt sulfide in Experimental Example 8 is 0.2A g -1 The discharge capacity at the current density. DETAILED DESCRIPTION

[0047] In order to make the technical problems, technical solutions and advantages to be solved by the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.

[0048] The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention. Without departing from the spirit and substance of the present invention, modifications or substitutions made to the methods, steps or conditions of the present invention are within the scope of the present invention.

[0049] Unless otherwise specified, the technical means used in the examples are conventional means well known to those skilled in the art; unless otherwise specified, the reagents used in the examples are commercially available.

[0050] Example 1 Preparation of carbon-composite nano-cobalt sulfide using organic clean cobalt slag in a short process.

[0051] S1. Prepare the organic clean cobalt slag and tap water in a liquid-to-solid ratio of 2:1, then adjust the pH value to 2 with dilute sulfuric acid, and stir at room temperature for 1 hour; filter to obtain the pickling leaching liquid and pickling slag, and dry the pickling slag in a forced air drying oven at 50°C for 2 hours.

[0052] S2, transporting the pickling leaching solution to the zinc electrodeposition system for zinc resource recovery, with a pickling slag yield of 30.61%;

[0053] S3. The pickled slag is placed in a nitrogen atmosphere and roasted. The temperature is raised to 120°C at a rate of 5°C / min and kept at this temperature for 1 hour. The temperature is then raised to 500°C at a rate of 5°C / min, kept at this temperature for 2 hours, and then naturally cooled to room temperature to obtain carbon composite nano-cobalt sulfide materials and organic gases such as carbon disulfide.

[0054] S4, transporting the organic gas such as carbon disulfide obtained in step S3 to the sodium thiamethoxam preparation system.

[0055] The process flow diagram of the preparation method is as follows Figure 1 As shown, the chemical reaction of acid removal of zinc in step S1 is as follows Figure 2 As shown, the mechanism diagram of preparing carbon composite nano-cobalt sulfide from pickled slag (mainly Fumei cobalt) in step S3 is as follows Figure 3 shown.

[0056] Experimental Example 1 The XRD pattern, TGA curve, Raman spectrum and TEM pattern of carbon composite nano-cobalt sulfide were investigated.

[0057] Figure 4 This is the XRD pattern of carbon composite nano-cobalt sulfide. The diffraction peaks at 2θ=30.16º, 35.18º, 46.76º, and 54.27º correspond to the (1111), (200), (211), and (311) crystal planes of CoS2 (JCPDS No: 42-0826), respectively. No other peaks were detected, indicating that the material has a high purity.

[0058] Figure 5 This is the TGA curve of carbon composite nano-cobalt sulfide in the temperature range from room temperature to 800 ℃ in air atmosphere, with a heating rate of 10 ℃ min -1 The weight loss in the range of 200-575 °C on the TGA curve corresponds to carbon oxidation and carbon dioxide generation, indicating that there is 12.1% carbon in the material.

[0059] Figure 6 The Raman spectrum of the material is at 1350 cm -1 The D peak nearby is related to the defects of carbon materials, 1590 cm -1 The nearby G peak is considered to be a sign of the presence of graphite carbon. The ratio of the G peak to the D peak height (IG / ID) is a sign of the graphitization degree of carbon materials. The IG / ID value of the obtained carbon composite nano-cobalt sulfide is 1.35, and the graphitization degree of the carbon layer is relatively high, which will significantly improve the conductivity of the material and improve the rate performance of the material.

[0060] Figure 7 This is the SEM image of the material. It can be seen from the SEM image that the material has a one-dimensional dot structure with a particle size of less than 30 nm, and is a nanodot particle.

[0061] Figure 8 The TEM image of the material shows that the particle size of carbon composite nano-cobalt sulfide is about 15-25 nm. The smaller nano size helps to increase the contact area between lithium ions and the material, reduce the diffusion path of ions, and alleviate the material pulverization caused by volume expansion. The outside of the cobalt sulfide is a typical amorphous carbon SEM image. The thickness of the carbon layer is about 10 nm. The amorphous carbon is tightly combined with the internal particles without obvious gaps, indicating that there is a chemical bond between the carbon layer and the internal substance.

[0062] Fig. 9 The EDS spectrum of the material is composed of Co, S, C, and N, with a C content of 9.24%, which is consistent with the TGA results. The N element and some S elements may be enriched in the carbon layer in the form of heteroatoms, which will help improve the specific capacity and rate performance of the carbon layer.

[0063] Fig.10 The XPS spectrum of the material is shown in Figure 2. The Co 2p high-resolution spectrum (a) has multiple peaks after peak separation. The two peaks at around 780 eV and 796 eV are attributed to Co. 2+ The two peaks at around 777 eV and 792 V are attributed to Co 3+ In addition, a pair of satellite peaks are observed at around 785 eV and 803 eV, indicating the diversity of valence states in CoS. The double peaks at 161.8 eV and 163.0 eV in Figure b are attributed to Co-S 2p 3 / 2 With Co-S 2p 1 / 2 , further illustrating the formation of cobalt sulfide, the double peaks at 164.1 eV and 165.3 eV are CS 2p 3 / 2 With 2p 1 / 2The signal peaks of 160.0 eV indicate that there is hybrid substitution of S atoms in the carbon layer. The single peak at 160.0 eV belongs to the signal peak of the CS-Co bond, indicating that there is a CS-Co interface bridge bond between the carbon layer of the material and the internal material interface. In the C 1s high-resolution spectrum of Figure c, the peaks at 284.8 eV, 285.3 eV, 286.4 eV, and 288.8 eV correspond to CC, CS, and CN, respectively, proving the co-doping of S and N on the surface of the carbon layer, which will lead to an increase in the active sites for lithium storage in the material and an improvement in conductivity. The high-resolution spectrum of N 1s in Figure d confirms the presence of nitrogen. The peaks with binding energies of 398.7 eV, 400.2 eV, and 401.1 eV are pyridinic nitrogen, pyrrolic nitrogen, and graphitic nitrogen in the carbon matrix, respectively, providing further evidence for the successful doping of nitrogen into carbon. Many studies on the effects of N and S heteroatoms on the electrochemical properties of electrode materials have shown that N atoms have the most obvious effect on improving electrochemical performance: graphitic nitrogen can improve the conductivity of materials, pyridinic nitrogen has more active sites and participates in pseudocapacitive reactions, and pyrrolic nitrogen increases active sites while achieving improved conductivity.

[0064] Experimental Example 2 The properties of carbon-composite nano-cobalt sulfide used as negative electrode material for ion batteries were investigated.

[0065] The carbon composite nano-cobalt sulfide prepared in Example 1 was mixed with carboxymethyl cellulose and conductive carbon black in a mass ratio of 70:15:15, and an appropriate amount of deionized water was added to make a slurry and applied to a copper foil. After the water evaporated, it was placed in a vacuum drying oven at 80°C for 12 hours, and then the copper foil coated with the active material was cut into a disc with a diameter of 12 mm. The disc with a diameter of 12 mm coated with the active material was used as the working electrode, the metal lithium was used as the counter electrode, and the Celgard 2400 composite membrane was used as the diaphragm, and the button cell was assembled in an oxygen-free gas glove box.

[0066] Fig.11 The electrode is made of carbon composite nano-cobalt sulfide. -1 The charge and discharge cycle performance curve under current density is 0.1 A·g -1 The current density of the first charge and discharge capacity is 2068.0 and 1512.7 mAh g -1, the first coulombic efficiency is 73.15%. The low coulombic efficiency is caused by irreversible side reactions such as the formation of SEI film. Generally, the higher the carbon content, the larger the specific surface area, and the worse the crystal integrity, the more SEI film is formed in the material. It is worth noting that the SEI film can protect the electrode material and reduce irreversible side reactions in subsequent charge and discharge cycles. The coulombic efficiency of the material reaches more than 98% after the fourth cycle and remains stable in subsequent cycles, indicating that the charge and discharge behavior of the sulfide nanodot composite material is highly reversible. After 100 cycles of charge and discharge, the discharge specific capacity is still as high as 1198.2 mAh g -1 , which is much higher than its theoretical value.

[0067] Fig.12 For materials at 2 A g -1 The charge and discharge cycle performance curve under current density is 2.0 A g -1 At the current density, the first charge and discharge specific capacity is 771.9 and 774.8 mAh g -1 The capacity increased before 200 cycles, which was due to the activation behavior of the material during the charge and discharge process. When the cycle reached 2000 cycles, the lithium storage capacity was 802.1 mAh g -1 . Visible 2.0 A g -1 The material has excellent stability under high current density.

[0068] Fig.13 For materials at 5A g -1 The charge and discharge cycle performance curve under current density is 5.0 A g -1 At the current density, the lithium storage capacity is 519.4 mAh g after 1500 cycles. -1 . Visible 5.0 A g -1 Even under high current density, the material still has good stability.

[0069] Fig.14 The charge and discharge cycle performance curves of the material at different current densities are 0.2, 0.5, 1.0, 2.0, 5.0, 10.0 and 15.0 A g -1 At the current densities, the discharge specific capacities of the materials are 1253.61, 1080.94, 924.8, 760.59, 538.11, 277.56 and 163.08 mAh g -1 , the current density is 15.0A g -1 Return to 0.2 A g -1 When the material discharge capacity is restored to 1080.53 mAh g -1, the capacity retention rate is high, indicating that the material still has good structural stability under high current density.

[0070] Comparative Example 1 Preparation of carbon-composite nano-cobalt sulfide by non-step-by-step heating.

[0071] S1. Prepare the organic clean cobalt slag and tap water in a liquid-to-solid ratio of 2:1, then adjust the pH value to 2 with dilute sulfuric acid, and stir at room temperature for 1 hour; filter to obtain the pickling leaching liquid and pickling slag, and dry the pickling slag in a forced air drying oven at 50°C for 2 hours.

[0072] S2, transporting the pickling leaching solution to the zinc electrodeposition system for zinc resource recovery;

[0073] S3, calcining the pickled slag in a nitrogen atmosphere, heating it to 500°C at a rate of 5°C / min, keeping it warm for 2 hours and then naturally cooling it to room temperature to obtain carbon composite nano-cobalt sulfide material and organic gases such as carbon disulfide.

[0074] S4, transporting the organic gas such as carbon disulfide obtained in step S3 to the sodium thiamethoxam preparation system.

[0075] Experimental Example 3 The XRD and SEM images of carbon composite nano-cobalt sulfide under non-step temperature increase conditions were examined.

[0076] Fig.15 The XRD diagram of the material prepared in Comparative Example 1 shows that the diffraction peaks at 2θ=30.16°, 35.18°, 46.76°, and 54.27° correspond to the (1111), (200), (211), and (311) crystal planes of CoS2 (JCPDS No. 42-0826), respectively. A very sharp peak also appears near 2θ=20.88°, which corresponds to the (001) crystal plane of CoO2 (JCPDS No. 89-8398), indicating that part of Co and O are combined during the inert high-temperature modification of PCoIBX. This indicates that part of the material is oxidized under non-step heating conditions.

[0077] Fig.16 This is the SEM image of the material. It can be seen from the SEM image that the material has a one-dimensional dot structure and the particle size is greater than 200 nm, which is much higher than the material obtained by step heating. The larger particle size is not conducive to the diffusion and transmission of lithium ions, and is not conducive to improving the effective capacity of the material. At the same time, it is easy to cause the material to pulverize, fall off and rapidly decay.

[0078] Experimental Example 4 The properties of carbon-composite nano-cobalt sulfide obtained by non-step temperature increase as negative electrode material for ion batteries were investigated.

[0079] The carbon composite nano-cobalt sulfide prepared in Comparative Example 1 was mixed with carboxymethyl cellulose and conductive carbon black in a mass ratio of 70:15:15, and an appropriate amount of deionized water was added to make a slurry and applied to a copper foil. After the water evaporated, it was placed in a vacuum drying oven at 80°C for 12 hours, and then the copper foil coated with the active material was cut into a disc with a diameter of 12 mm. The disc with a diameter of 12 mm coated with the active material was used as the working electrode, the metal lithium was used as the counter electrode, and the Celgard 2400 composite membrane was used as the diaphragm, and the button cell was assembled in an inert gas glove box.

[0080] Fig.17 The electrode is made of carbon composite nano-cobalt sulfide. -1 The charge and discharge cycle performance curve under current density is 0.1 A·g -1 The current density of the first charge and discharge capacity is 1140.3 and 857.7 mAh g -1 , which is much lower than the material obtained in Example 1. The lower capacity is due to the poor conductivity of cobalt oxide, which reduces the transmission speed of lithium ions in the material. On the other hand, the larger particle size of the material increases the rough function path of lithium ions, thereby reducing the reaction kinetics of the material. In addition, the lithium storage capacity of the material decays rapidly during the charge and discharge cycle, which is due to the fact that the larger particles are easily pulverized and fall off due to the insertion and extraction of lithium ions.

[0081] Comparative Example 2 Preparation of carbon-composite nano-cobalt sulfide at low temperature without step-by-step heating.

[0082] S1. Prepare the organic clean cobalt slag and tap water in a liquid-to-solid ratio of 2:1, then adjust the pH value to 2 with dilute sulfuric acid, and stir at room temperature for 1 hour; filter to obtain the pickling leaching liquid and pickling slag, and dry the pickling slag in a forced air drying oven at 50°C for 2 hours.

[0083] S2, transporting the pickling leaching solution to the zinc electrodeposition system for zinc resource recovery;

[0084] S3. The pickled slag is placed in a nitrogen atmosphere and roasted, the temperature is raised to 300° C. at a rate of 5° C. / min, and then naturally cooled to room temperature after being kept at this temperature for 2 hours to obtain carbon composite nano-cobalt sulfide materials and organic gases such as carbon disulfide.

[0085] S4, transporting the organic gas such as carbon disulfide obtained in step S3 to the sodium thiamethoxam preparation system.

[0086] Experimental Example 5 The SEM image of carbon composite nano-cobalt sulfide prepared at low temperature by non-step heating was examined.

[0087] Fig.18This is the SEM image of the material prepared in Comparative Example 2. It can be seen from the SEM image that the material has a flaky structure and a particle size greater than 200 nm. The larger particle size and flaky structure may be due to incomplete carbonization of the precursor.

[0088] Experimental Example 6 The characteristics of carbon composite nano-cobalt sulfide prepared at low temperature without step-by-step heating were investigated for use as negative electrode materials for ion batteries.

[0089] The carbon composite nano-cobalt sulfide prepared in Comparative Example 2 was mixed with carboxymethyl cellulose and conductive carbon black in a mass ratio of 70:15:15, and an appropriate amount of deionized water was added to make a slurry and applied to a copper foil. After the water evaporated, it was placed in a vacuum drying oven at 80°C for 12 hours, and then the copper foil coated with the active material was cut into a disc with a diameter of 12 mm. The disc with a diameter of 12 mm coated with the active material was used as the working electrode, the metal lithium was used as the counter electrode, and the Celgard 2400 composite membrane was used as the diaphragm, and the button cell was assembled in an inert gas glove box.

[0090] Fig.19 The electrode made of this material has a -1 The charge and discharge cycle performance curve under current density is 0.2A·g -1 The current density of the first charge and discharge capacity is 1438.2 and 602.6 mAh g -1 The coulombic efficiency in the first cycle is low, and the capacity after the cycle is much lower than that of the material obtained in Example 1. The lower capacity is due to incomplete carbonization and excessive side reactions.

[0091] Comparative Example 3 Preparation of carbon composite nano-cobalt sulfide at high temperature without step-by-step heating.

[0092] S1. Prepare the organic clean cobalt slag and tap water in a liquid-to-solid ratio of 2:1, then adjust the pH value to 2 with dilute sulfuric acid, and stir at room temperature for 1 hour; filter to obtain the pickling leaching liquid and pickling slag, and dry the pickling slag in a forced air drying oven at 50°C for 2 hours.

[0093] S2, transporting the pickling leaching solution to the zinc electrodeposition system for zinc resource recovery;

[0094] S3. The pickled slag is calcined in a nitrogen atmosphere, the temperature is raised to 700° C. at a rate of 5° C. / min, and the mixture is kept at this temperature for 2 hours and then naturally cooled to room temperature to obtain carbon composite nano-cobalt sulfide material and organic gases such as carbon disulfide.

[0095] S4, transporting the organic gas such as carbon disulfide obtained in step S3 to the sodium thiamethoxam preparation system.

[0096] Experimental Example 7 SEM images of carbon composite nano-cobalt sulfide prepared at high temperature by non-step heating.

[0097] Fig. 20This is the SEM image of the material prepared in Comparative Example 3. It can be seen from the SEM image that the material has a spherical structure and a particle size greater than 1000 nm. The larger particle size may be due to the partial melting and polymerization of cobalt sulfide at high temperature.

[0098] Experimental Example 8 The characteristics of carbon composite nano-cobalt sulfide prepared at high temperature without step-by-step heating were investigated for use as negative electrode materials for ion batteries.

[0099] The carbon composite nano-cobalt sulfide prepared in Comparative Example 3 was mixed with carboxymethyl cellulose and conductive carbon black at a mass ratio of 70:15:15, and an appropriate amount of deionized water was added to make a slurry and applied to a copper foil. After the water evaporated, it was placed in a vacuum drying oven at 80°C for 12 hours, and then the copper foil coated with the active material was cut into a disc with a diameter of 12 mm. The disc with a diameter of 12 mm coated with the active material was used as the working electrode, the metal lithium was used as the counter electrode, and the Celgard 2400 composite membrane was used as the diaphragm, and the button cell was assembled in an inert gas glove box.

[0100] Fig.21 The electrode is made of carbon composite nano-cobalt sulfide, at 0.2A g -1 The charge and discharge cycle performance curve under current density is 0.2 A·g -1 The current density of the first charge and discharge capacity is 376.1 and 332.6 mAh g -1 The low capacity is due to the fact that the particles are too large, lithium ions cannot be transmitted to the interior of the material, and the actual lithium storage material is far lower than the theoretical value.

[0101] The above is only a preferred embodiment of the present invention, and the protection scope of the present invention is not limited to the above embodiments. For those skilled in the art, improvements and changes obtained without departing from the technical concept of the present invention should also be regarded as the protection scope of the present invention.

Claims

1. A method for preparing carbon composite nano cobalt sulfide by short process of organic clean cobalt slag, characterized in that: The following steps are involved: S1. A pickling process removes zinc and other elements in the organic clean cobalt slag to obtain a pickling leaching solution and pickling slag; S2, transporting the pickling leaching solution obtained in S1 to a zinc electrodeposition system for zinc resource recovery; S3, placing the pickled slag obtained in S1 in an oxygen-free atmosphere and roasting it in two stages and then cooling it naturally to obtain a carbon composite nano-cobalt sulfide material and an organic gas; S4, transporting the organic gas obtained in S3 to a sodium fumei preparation system; In the step S3, the heating rate of the first stage of the two-stage calcination is 1-5°C / min, and the temperature is raised to 120°C and kept for 1 hour. By removing the moisture and oxygen source in the system before the decomposition of the cobalt iodide, the occurrence of nitrogen oxide and sulfur oxide generation reaction is avoided; the heating rate of the second stage of calcination is 1-10°C / min, and the temperature is raised to 500°C and kept for 2 hours.

2. The method according to claim 1, characterized in that: The oxygen-free atmosphere in the step S3 includes nitrogen or argon.

3. Use of carbon composite nano-cobalt sulfide prepared by the method according to any one of claims 1 to 2 in the preparation of high-performance battery materials.

4. The use according to claim 3, characterized in that: The battery material is an ion battery negative electrode material.

Citation Information

Patent Citations

  • Difunctional oxygen electrocatalyst as well as preparation method and application thereof

    CN117117220A